Epidemiology of cattle diseases in the northeast of La Pampa, Argentina - Miranda, A. O. (Revista Veterinaria, 2016)
A cross-sectional survey was carried out on 350 farms in the north east of La Pampa Province, Argentina. The goal was to record the prevalence of cattle diseases reported by farmers. Farms wereA stratified into three categories on the basis of adult herd size (300 to 500 cattle, 500 to 900 cattle and greater than 900 cattle) and a random sample selected from each strata. According to the productive system, farms were classified as fattening (F), cow-calf (C) and cow-calf-fattening (CF). Presented data are part of a comprehensive survey on cattle farms performed by INTA and Ministry of Production staff. The information described on this assay corresponds to principal signs and health problems recorded in different farms. Actinosis (n=115 farms), bovine respiratory diseases (BRD) (n=77), neonatal calf diarrhea (NCD) (n=60), copper deficiency (n=54), and blackleg, gas gangrene and enterotoxaemia (BGE) (n=39) were the main diseases. NCD and BGE were geographically distributed on the southern half area, while actinosis, copper deficiency and pneumonia were distributed on the central-west area. BRD also showed a second risk area on the northwest. According to production system, BRD was found to be associated to F, while NCD, copper deficiency and BGE were associated to CF. According to strata level, no differences were found for any diseases considered for the present essay.